C-myc oncogene expression in anal squamous neoplasia. Issue 1 (January 1993) - Ogunbiyi, O A; Scholefield, J H; Rogers, K; Sharp, F; Smith, J H; Polacarz, S V
Abstract : AIMS: To determine the pattern of c-myc oncogene expression in anal squamous neoplasia and to determine if this could be used as a marker of disease progression. METHODS: The presence and localisation of the c-myc gene product p62 in archival specimens of anal squamous epithelium, normal and neoplastic, was examined using immunohistochemical staining with the monoclonal antibody Myc1-6E10. Ten normal and epithelia, 10 anal intraepithelial neoplasia (AIN) III, and 31 anal squamous cancers were examined. RESULTS: There was a noticeable difference between the staining characteristics of invasive tumours, normal anal epithelium, and AIN III. Intense, diffuse, mixed nuclear and cytoplasmic (n = 14) and exclusively nuclear (n = 8) staining in 22 of 31 (71%) of invasive anal tumours was observed. All positively staining tumours were well differentiated histologically, while the negatively staining nine of 31 (29%) were poorly differentiated (n = 7) and moderately well differentiated (n = 2). In six positively staining tumour sections adjacent areas of AIN III and non-dysplastic anal epithelium had staining characteristics similar to those of the invasive component. Staining in both normal anal epithelium (4/10) and AIN III specimens obtained from patients without a history of invasive disease (8/10) was less intense, focal in distribution, and exclusively nuclear. No difference in staining characteristics could be detected in these two groups. CONCLUSIONS: The results of this study suggest that c-myc oncogene expression is implicated in the pathogenesis of anal squamous neoplasia, and that immunohistochemical staining for c-myc protein may be helpful in identifying those AIN III lesions most likely to progress to invasive tumours.